Molecular Study of Fimh Gene in Klebisella Pneumoniae Isolated From Urinary Catheter Patients - Israa Abdul Ameer Al-Kraety1, Zahraa Hameed Oda Alquraishi2, Aqeel A Alsadawi3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
This study aimed to isolate and diagnose K. pneumoniae from clinical specimens of urine from urinary catheterized patients and molecular Detection of FimH fimbrial adhesin in Klebisella pneumonia in Najaf governorate from October 2018 to March 2019, which includes 40 clinical specimens (urine). The diagnosis of K. pneumoniae isolates was based on culture and biochemical characteristics as an initial diagnosis. The final diagnosis by the Vitek-2 compact system is automated besides the use of PCR technique to detect on fimH fimbrial adhesion gene. The biochemical results showed that 40/40 isolates gave positive result of K. pneumoniae.These results were confirmed by Vitek showed that 40/40 were positive for K. pneumoniae isolated and PCR technique by using fimH gene where 14/40 were positive for K. pneumoniae isolated from urine urinary catheterized patients. The study, which was conducted in the diagnosis of bacteria, concluded that the technique of compact Vitek-2 automated. The ability of bacteria to stick to the formation of biofilm was investigated by phenotypic method.